Pengaruh Metode Retelling dalam Meningkatkan Keterampilan Berbicara Siswa Sekolah Dasar Fase C - Rahmawati, Siti; Giwangsa, Sendi Fauzi (AS-SABIQUN, 2025)
Speaking ability is a key element of language skills in elementary school education that contributes to students' academic and social development. However, this skill often receives less attention in the learning process. This study aims to examine the effect of the retelling method on improving the speaking skills of Phase C elementary school students. The research employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The sample consisted of 10 randomly selected fifth-grade students. The research instrument was a speaking skills rubric measuring five main aspects: fluency, diction, sentence structure, comprehension, and communicative aspects. Data were analyzed using a paired t-test to evaluate significant differences between the pretest and posttest results. The findings showed that the retelling method had a significant impact on improving students' speaking skills. The average pretest score of 57.50 increased to 76.50 in the posttest, with a significant difference (p < 0.001). This method not only enhanced students' speaking abilities but also reduced their anxiety in public speaking. The study concluded that the retelling method effectively improved the speaking skills of Phase C elementary school students and is therefore recommended for integration into learning. Additionally, this research opens opportunities to develop the implementation of the retelling method by utilizing digital technology for more optimal results.